2016
DOI: 10.1177/0306624x15589091
|View full text |Cite
|
Sign up to set email alerts
|

Offspring-Perpetrated Familicide

Abstract: The majority of studies examining familicide involve the male head of the family killing his wife or intimate partner and children. Little research exists on familicide cases involving children killing one or both parents plus other family members (siblings, grandparents, etc.). This study used the National Incident-Based Reporting System, which currently contains arrest data for about 25% of the U.S. population, to examine familicide incidents perpetrated by adult and juvenile offenders over the 20-year perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…We published a case report on the patient with bipolar disorder who killed her mother [58]. It should be noted that many cases of matricide are not associated with mental disorders [59]. There was just one case of personality disorder, while most of the sample has been involuntarily committed because of more severe forms of mental disease.…”
Section: Discussionmentioning
confidence: 99%
“…We published a case report on the patient with bipolar disorder who killed her mother [58]. It should be noted that many cases of matricide are not associated with mental disorders [59]. There was just one case of personality disorder, while most of the sample has been involuntarily committed because of more severe forms of mental disease.…”
Section: Discussionmentioning
confidence: 99%
“…Among clinical factors, an antisocial personality is one of the main risk factors for parricides among juveniles and it is often related with familicides involving parents and other kin [ 3 , 27 ]. It has been observed that children who have grown up in dysfunctional families are at greater risk to develop a conduct disorder, which is a precursor of an antisocial personality disorder [ 2 , 28 – 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cases were retrieved by searching the phrases "murder," "family murder" and "parricide." This type of methodology has been successfully used by a number of previous researchers (Adinkrah, 2017;Boots & Heide, 2006;Fegadel & Heide, 2017;Govender, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Once the victims are dead, the need for taking his/her own life is removed (Liem & Reichelmann, 2014). Diffuse conflict familicides involve the prevalence of conflicts in diverse constellations of victims, often including a spouse and in-laws, parents, and other family members (Fegadel & Heide, 2017).…”
Section: Prior Work On Multiple-victim Parricidesmentioning
confidence: 99%